2023
DOI: 10.1038/s41598-023-29012-1
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on skin tumors of the elderly in a community in Shanghai, China

Abstract: The morbidity of skin tumors (ST) in China is a great concern as the population ages. No epidemiological survey on ST in elderly communities in China has been reported. A questionnaire survey was conducted among the residents over 60 years old in a community in Shanghai, China from May 1, 2011 to November 30, 2011. The prevalence of cutaneous tumors and associated factors were analyzed. Among 2038 valid cases, a total of 78 (3.8%, 95% CI 3.0–4.7) skin cancers (SC) were confirmed. According to the final multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Specifically, the incidence of cSCC has been reported to be 5 to 10 times higher in people over 75 years of age than in people under 55, and as much as 50 to 300 times higher in people under 45 [ 35 37 ]. Moreover, a survey of residents over 60 in a community in Shanghai, China, found that skin cancer tended to increase with age, especially in groups over 75 years old [ 38 ]. Patients with cSCC may exhibit more chronic sun injury, leading to experiencing multiple cSCCs across their lives, which could be linked to specific patterns of total and cumulative UV exposure [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the incidence of cSCC has been reported to be 5 to 10 times higher in people over 75 years of age than in people under 55, and as much as 50 to 300 times higher in people under 45 [ 35 37 ]. Moreover, a survey of residents over 60 in a community in Shanghai, China, found that skin cancer tended to increase with age, especially in groups over 75 years old [ 38 ]. Patients with cSCC may exhibit more chronic sun injury, leading to experiencing multiple cSCCs across their lives, which could be linked to specific patterns of total and cumulative UV exposure [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of various types of melanoma is linked with UV radiation exposure patterns . Long-term susceptibility such as occupational outdoor exposure is frequently linked to SCC and BCC SC. , The superficial BCC usually appears on the trunk . As compared to SCC, melanoma is commonly associated with irregular exposure .…”
Section: Skin Cancer Occurs Due To the Involvement Of Various Factorsmentioning
confidence: 99%